Guinea : Background Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This Background Paper on Guinea highlights that Guinea's relatively strong macroeconomic performance during 1987-94 allowed for an annual increase in real per capita GDP of 1 percent. On the basis of national account estimates, the growth of value added in the primary sector averaged about 3.7 percent annually during 1986-92 before accelerating to some 5 percent during 1993-94. The buoyancy in the primary sector reflected mainly a strong response of agriculture to economic liberalization and large investments in the agricultural sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet